Is Firm Value Affected by Financial Ratios in Manufacture Companies? - Mas’adah, Ninik (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research aims to examine the influence of profitability, leverage, company size, and dividend policy on the value of the manufacturing companies studied in various industries. This research employs a quantitative approach. The sampling technique used is purposive sampling. Thus, 45 samples were taken from manufacturing companies in various industrial sectors listed on the IDX for the 2021–2023 period. The data analysis program using SmartPLS. The results of this research show that liquidity has a positive and negligible effect on company value, leverage has a positive and significant effect on company value, and company size has a negative and insignificant effect on company value. Profitability has a positive and partially significant effect on company value, and dividend policy has a positive and partially significant effect on company value.